Alcohol consumption and its relationship with parental parenting in adolescents in Michoacán, México - Anzo Hernández, Anabella (2022)
Objective: To establish relationship between alcohol consumption and parental upbringing in adolescents from Michoacán localities. Method: Quantitative study with correlational and cross-sectional design; with a non-probabilistic convenience sample of 150 adolescents from different localities of Michoacán state, México. Instruments: AUDIT test (α=0.86) Standards and Requirements Scale (ENE Spanish scronym) (α=0.90). Descriptive statistics and the program SPSS v.25 were used in the analysis of the information. The right to privacy was respected. Main results: From the sample 54.2% were women, 97.9% were singles, 40% were residents of Morelia and the mean age was 15.93 years (DE= 1.55).  It was found that there was no risk in the alcohol consumption up to 85.4 % of the sample and that 9.4% of men and 5.2% of women presented physical-psychological problems due to alcohol consumption. In parental upbringing, the maximum level of demand was identified in 80.2%, 54.2% undemocratic parenting style, 64.6% non-authoritarian parenting style and 97.9% non-permissive parenting style. A statistically significant relationship was found between alcohol consumption and parental upbringing and authoritarian and permissive styles (p>0.05). General Conclusion: Eight out of 10 adolescents were not at risk for alcohol consumption, with the highest level of demand in parental upbringing. This information will serve as the basis to propose preventive strategies with the family of adolescents.